Cephalopod Behavior: From Neural Plasticity to Consciousness - Ponte, Giovanna; Chiandetti, Cinzia; Edelman, David B.; Imperadore, Pamela; Pieroni, Eleonora Maria; Fiorito, Graziano (Frontiers in Systems Neuroscience, 2022)
It is only in recent decades that subjective experience - or consciousness - has become a legitimate object of scientific inquiry. As such, it represents perhaps the greatest challenge facing neuroscience today. Subsumed within this challenge is the study of subjective experience in non-human animals: a particularly difficult endeavor that becomes even more so, the further one crosses the great phylogenetic divide between vertebrate and invertebrate phyla. Here, we explore the possibility of consciousness in one group of invertebrates - cephalopod molluscs. We believe such a review is timely, particularly considering cephalopods’ impressive learning and memory abilities, richness of behavioral repertoire, and the relative complexity of their nervous systems and sensory capabilities. Indeed, in some cephalopods, these abilities are so sophisticated that they are comparable to those of some higher vertebrates. Following the criteria and framework outlined for the identification of hallmarks of consciousness in non-mammalian species, we propose here that cephalopods - particularly the octopus - provide a unique test case among invertebrates for examining the properties and conditions that, at the very least, afford a basal faculty of consciousness. These include, among others: i. discriminatory and anticipatory behaviors indicating a strong link between perception and memory recall; ii. the presence of neural substrates representing functional analogs of thalamus and cortex; iii. neurophysiological dynamics resembling the functional signatures of conscious states in mammals. We highlight the current lack of evidence as well as potentially informative areas that warrant further investigation to support the view expressed here. Finally, we identify future research directions for the study of consciousness in these tantalizing animals.